2022
DOI: 10.1177/23259671211071146
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Patch Augmentation on Rotator Cuff Repair: A Systematic Review and Meta-analysis

Abstract: Background: Despite technological advances, the overall retear rate on rotator cuff repair is still high. Patches have shown significant reduction in retear rate and pain scores; however, this is not a universal finding and conflicting results have been shown among functional shoulder scales. Purpose: To analyze previous controlled trials of the literature to bring a consensus about the effectiveness of patch use on rotator cuff repair. Study Design: Systematic review; Level of evidence, 1. Methods: The search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Arthroscopic rotator cuff patch augmentation or interposition surgery has grown in popularity over the years, with systematic reviews and meta-analysis showing that these methods provide better shoulder scores compared with rotator cuff repair alone. 15 , 16 A variety of grafts are available, ranging from xenograft, synthetic grafts, autograft, and allograft. 10 Xenografts that were available included porcine dermal xenograft; however, these grafts were associated with severe inflammatory reactions, and Flury et al.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic rotator cuff patch augmentation or interposition surgery has grown in popularity over the years, with systematic reviews and meta-analysis showing that these methods provide better shoulder scores compared with rotator cuff repair alone. 15 , 16 A variety of grafts are available, ranging from xenograft, synthetic grafts, autograft, and allograft. 10 Xenografts that were available included porcine dermal xenograft; however, these grafts were associated with severe inflammatory reactions, and Flury et al.…”
Section: Discussionmentioning
confidence: 99%
“…The relative efficacy of various patch options, including allografts, xenografts, synthetic polymers, and autografts, remains unproven. 4 Clinical outcomes assessment of the biphasic interpositional allograft is ongoing.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…In terms of re-tear rate, patch augmentation in rotator cuff repair showed a lower rate than repair without patch augmentation, according to a recent meta-analysis study [ 9 ]. However, the effect on clinical outcomes was not clinically meaningful.…”
mentioning
confidence: 99%
“…de Andrade et al [ 9 ] found that the range of shoulder-forward flexion tended to be lower with patch augmentation. Choi et al [ 10 ] reported that clinical outcomes and range of shoulder motion did not differ between the patch augmentation group and repair only group.…”
mentioning
confidence: 99%